The Impact of Dry Atmospheric Deposition on the Sea-Surface Microlayer in the SE Mediterranean Sea: An Experimental Approach - Astrahan, Peleg; Herut, Barak; Paytan, Adina; Rahav, Eyal (Frontiers in Marine Science, 2016)
The oligotrophic southeastern Mediterranean Sea (SEMS) is frequently exposed to desert-dust deposition which supplies nutrients, trace metals and a wide array of viable airborne microorganisms. In this study, we experimentally examined the impact of aerosol addition, collected during an intense dust storm event in early September 2015, on the biomass and activity of pico-phytoplankton and heterotrophic bacterial populations at the sea-surface micro layer (SML) relative to the sub surface layer (SSL). Aerosol (1.5 mg L-1) was added to SML and SSL water samples in microcosms (4.5 L) and the water was frequently sampled over a period of 48 hours. While the aerosol amendment triggered a moderate 1.5-2 fold increase in primary production in both the SML and the SSL, bacterial production increased by ~3 and ~7 folds in the SSL and SML, respectively. Concurrently, the abundance and flow-cytometric characteristics (green fluorescence and side scatter signals) of high nucleic acid (HNA) and low nucleic acid (LNA) bacterial cells showed a significant increase in the %HNA, in both SML and SSL samples following aerosol amendment. This shift in nucleic acid content took place at a much faster rate in the SML, suggesting a more active heterotrophic community. These changes were likely a result of higher rates of carbon utilizations in the SML following the dust addition, as assessed by a selected hydrocarbons and saccharides analysis. Additionally, a high absorption rate of hydrocarbons by the aerosol particles was measured following the additions, leaving less than 10% of these molecules available for potential heterotrophic microbial utilization. Our results suggest that the heterotrophic microbial community inhabiting the SML is more efficient in utilizing aerosol associated constituents than the community in the SSL.